Effect of cardiac surgery on maternal and perinatal outcome in rheumatic heart disease with pregnancy: a comparative study - Yadav, Vikas; Sharma, J. B.; Kachhawa, Garima; Kriplani, Alka; Mahey, Reeta; Dalal, Venus; Kriplani, Isha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Rheumatic heart disease remains the commonest heart disease in India with mitral stenosis being the most common lesion and is associated with significant maternal and perinatal mortality and morbidity. The objective of this study was to compare maternal and perinatal outcome in women with rheumatic heart valvular disease who had no surgery or had percutaneous balloon mitral valvuloplasty (PBMV) or had valvular replacement surgery. Methods: It was a retrospective study in 113 women with rheumatic heart disease with various valvular lesion admitted in the hospital in previous 10 years. There were 58 (51.35%) patients without cardiac surgery (Group 1), 24 (21.23%) with PTMC (Group 2) and 31 (27.43%) with valve replacement surgery (Group 3). Maternal and perinatal outcome were compared in three groups. Results: The baseline characteristics were similar in the three group. In cardiac complications New York Heart Association (NYHA) deterioration was significantly higher (24.1%) in non-operated group (Group 1) as compared to Group 2 (12.3%) and Group 3 (16.1%). There was no difference in Group 2 and Group 3. Need of cardiac medication (digoxin) was also highest (67.2%) in Group 1 as compared to Group 2 (24.6%) (p = 0.002) and Group 3 (38.7%) (p = 0.001) but no difference in Group 2 and Group 3. Anticoagulant were given to significantly higher number (54.8% of cases in Group 3 (valve replacement) as compared to Group 1 (3.4%) and Group 2 (12.5%). There was no significant difference in obstetric events and mode of delivery in the three groups. Similarly, there was no difference in fetal outcome in the three groups as regard to mean birth weight, APGAR score, fetal growth restriction, fetal or neonatal death or congenital anomalies in the three groups. Conclusions: Cardiac surgery before or during pregnancy did not significantly improve maternal or perinatal outcome. Only cardiac events and need of medication was reduced with surgery. Hence surgery should be performed judiciously in selected cases.